Influência da corrente de soldagem e da composição do metal de adição sobre o comportamento mecânico de juntas soldadas dissimilares - Nova, Antonio Marcos Vila (2018)
Failures in dissimilar joints of underwater structures have occurred. Several researches have been developed to determine the best welding procedure that results in a welded joint with mechanical properties appropriate for application in such aggressive environments mechanically and chemically. This work has as main objective to evaluate the influence of current mode and type of addition metal on the mechanical behavior of dissimilar joints of SAE 4130 steel previously buttery with nickel alloys and welded to ASTM A36 steel. The influence variables were the welding current mode (conventional and pulsed) and the type of addition metals, AWS ERNiCrMo-3 (Inconel 625) and AWS ERNiCrMo-15 (Inconel 725) wires. As response variables, mechanical strength, hardness and impact toughness were analyzed at the interface of dissimilar joints, a critical region. The results were characterized by mechanical tests and microscopy (MO, MEV). The results show that the mechanical behavior of the butterysubstrate interface is influenced by the welding current and by the type of addition metal; the results also showed the welding procedure with Inconel 625 and pulsed current showed to be more appropriate for the mechanical properties studied.